ANALISIS EFISIENSI EKONOMI PENGGUNAAN FAKTOR PRODUKSI PADI SAWAH DI DESA SUKOREJO KECAMATAN SUKOREJO, KABUPATEN PONOROGO - Nasrullah Aziz (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
AbstractThe increase in the volume of rice imports from 2013-2016 in Indonesia reached 97.45%, this was done by the government in order to meet the need for rice due to domestic rice production that was unable to meet the level of consumption of Indonesian people for rice. This study aims at the level of technical efficiency, allocative efficiency and economic efficiency of rice farming. The results showed that seeds, urea fertilizer and labor were factors of production that significantly affected the yield of technically produced paddy rice. However, the seeds and urea fertilizer in its application are still not allocatively efficient, therefore it must be added to the production factor while the labor factor has exceeded the optimal production line so that the workforce must be reduced, so that rice farming cannot be said to be efficient.Keywords: efficiency, lowland rice